[INVITED] State of the art of Brillouin fiber-optic distributed sensing. (April 2016) - Motil, Avi; Bergman, Arik; Tur, Moshe
Abstract: Fiber-optic distributed sensing, employing the Brillouin effect, is already a commercially available measurement technique for the accurate estimation of the static strain/temperature fields along tens of kilometers with a spatial resolution of the order of a meter. Furthermore, relentless research efforts are paving the way to even much wider usability of the technique through recently achieved enhanced performance in each of its critical dimensions: measurement range has been extended to hundreds of kilometers; spatial resolution is of the order of a centimeter or less, signal to noise ratio has been significantly improved; fast dynamic events can be captured at kHz's sampling rates; and a much better understanding of the underlying physics has been obtained, along with the formulation of figures of merit, and the preparation and early adoption of appropriate standards and guidelines. This paper describes the basics, as well as the state of the art, of the leading Brillouin interrogation methods, with emphasis on the significant progress made in the last 3 years. It also includes a short introduction to coding, which has proven instrumental in many of the recently obtained performance records. Highlights: Brillouin-based fiber-optic distributed sensing is a leading technique for the monitoring of strain, temperature and related measurands Recent research has pushed its performance to new records. Sensing range has been extended to hundreds of kilometers. Spatial resolution is down to a centimeter. It can now monitor fast dynamic events.